Cryo-EM samples of gas-phase purified protein assemblies using native electrospray ion-beam deposition. (6th September 2022) - Esser, Tim K.; Böhning, Jan; Fremdling, Paul; Bharat, Tanmay; Gault, Joseph; Rauschenbach, Stephan
Abstract : Cryo-EM of samples prepared from mass-selected and soft-landed protein complexes creates a direct link between structure and complementary chemical information. Abstract : An increasing number of studies on biomolecular function indirectly combine mass spectrometry (MS) with imaging techniques such as cryo electron microscopy (cryo-EM). This approach allows information on the homogeneity, stoichiometry, shape, and interactions of native protein complexes to be obtained, complementary to high-resolution protein structures. We have recently demonstrated TEM sample preparation via native electrospray ion-beam deposition (ES-IBD) as a direct link between native MS and cryo-EM. This workflow forms a potential new route to the reliable preparation of homogeneous cryo-EM samples and a better understanding of the relation between native solution-phase and native-like gas-phase structures. However, many aspects of the workflow need to be understood and optimized to obtain performance comparable to that of state-of-the-art cryo-EM. Here, we expand on the previous discussion of key factors by probing the effects of substrate type and deposition energy. We present and discuss micrographs from native ES-IBD samples with amorphous carbon, graphene, and graphene oxide, as well as landing energies in the range between 2 and 150 eV per charge.